How can neurophysiological studies help with movement disorders characterization in clinical practice? A review - Talyta GRIPPE; Natalia Spinola Costa da CUNHA; Pedro Renato de Paula BRANDÃO; Rubens Nelson Morato FERNANDEZ; Francisco Eduardo Costa CARDOSO (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Neurophysiological studies are ancillary tools to better understand the features and nature of movement disorders. Electromyography (EMG), together with electroencephalography (EEG) and accelerometer, can be used to evaluate a hypo and hyperkinetic spectrum of movements. Specific techniques can be applied to better characterize the phenomenology, help distinguish functional from organic origin and assess the most probable site of the movement generator in the nervous system. Objective: We intend to provide an update for clinicians on helpful neurophysiological tools to assess movement disorders in clinical practice. Methods: Non-systematic review of the literature published up to June 2019. Results: A diversity of protocols was found and described. These include EMG analyses to define dystonia, myoclonus, myokymia, myorhythmia, and painful legs moving toes pattern; EMG in combination with accelerometer to study tremor; and EEG-EMG to study myoclonus. Also, indirect measures of cortical and brainstem excitability help to describe and diagnose abnormal physiology in Parkinson's disease, atypical parkinsonism, dystonia, and myoclonus. Conclusion: These studies can be helpful for the diagnosis and are usually underutilized in neurological practice.